Students’ Perceptions of Gemini Ai Effectiveness in Academic Writing - Azmi, Khairul; Fithriani , Rahmah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research investigates students' perceptions of the effectiveness of Gemini AI in English academic writing, addressing the gap in the literature on AI-powered writing tools for EFL students. A qualitative case study involving 26 English education students from a university in North Sumatra explored how Gemini AI impacts their academic writing. Data was collected through questionnaires, analysis of students' academic writing files, and semi-structured interviews. The findings highlight the significant impact of Gemini AI on students' academic writing, particularly in improving structure, coherence, and revision skills. The study also reveals challenges related to source attribution and plagiarism concerns. This study contributes valuable insights into the potential of AI-powered tools like Gemini to enhance EFL students' academic writing capabilities and provides practical implications for educators and developers.